Characterization of Gut Microbiome in the Mud Snail Cipangopaludina cathayensis in Response to High-Temperature Stress - Yang-Yang Wu; Chun-Xing Cheng; Liu Yang; Quan-Qing Ye; Wen-Hong Li; Jiao-Yun Jiang (Animals, 2022)
The mud snail Cipangopaludina cathayensis is a widely distributed species in China. Particularly in Guangxi province, mud snail farming contributes significantly to the economic development. However, global warming in recent decades poses a serious threat to global aquaculture production. The rising water temperature is harmful to aquatic animals. The present study explored the effects of high temperature on the intestinal microbiota of C. cathayensis. Snail intestinal samples were collected from the control and high-temperature groups on days 3 and 7 to determine the gut microbiota composition and diversity. Gut bacterial community composition was investigated using high-throughput sequencing of the V3–V4 region of bacterial 16S rRNA genes. Our results suggested that thermal stress altered the gut microbiome structure of C. cathayensis. At the phylum level, Proteobacteria, Bacteroidetes, and Firmicutes were dominant in C. cathayensis gut microbiota. The T2 treatment (32 ± 1 °C, day 7) significantly decreased the relative abundance of Firmicutes, Actinobacteria, and Deinococcus-Thermus. In T2, the abundance of several genera of putatively beneficial bacteria (Pseudomonas, Aeromonas, Rhodobacter, and Bacteroides) decreased, whereas the abundance of Halomonas—a pathogenic bacterial genus—increased. The functional prediction results indicated that T2 treatment inhibited some carbohydrate metabolism pathways and induced certain disease-related pathways (e.g., those related to systemic lupus erythematosus, Vibrio cholerae infection, hypertrophic cardiomyopathy, and shigellosis). Thus, high temperature profoundly affected the community structure and function of C. cathayensis gut microbiota. The results provide insights into the mechanisms associated with response of C. cathayensis intestinal microbiota to global warming.